A systematic review of cultural adaptations in the global application of ABA‐based telehealth services. Issue 4 (20th September 2020) - Sivaraman, Maithri; Fahmie, Tara A.
Abstract : With telehealth gaining acceptance as a service delivery method, behavior analysts are now providing services to individuals worldwide. This review highlights the cultural adaptations used in ABA‐based telehealth treatments for individuals with ASD outside of the United States. Nine studies met our inclusion criteria and the data were synthesized narratively. All studies reported some type of cultural adaptation, with most studies reporting changes made to the service delivery method. This included using translated materials; training in the language of the client; and matching the trainer in birthplace, ethnicity, or gender with the participants. The adaptations described in published research can serve as a resource for behavior analysts who have interest in global telehealth services. However, given the emerging nature of this area of research, it is challenging to know which adaptations are necessary to achieve optimal outcomes. The review concludes with ideas for research development in this area.